2016
DOI: 10.1682/jrrd.2015.02.0023
|View full text |Cite
|
Sign up to set email alerts
|

Transfer component skill deficit rates among Veterans who use wheelchairs

Abstract: Abstract-The purpose of this study was to quantify the deficit rates for transfer component skills in a Veteran cohort and explore the relationship between deficit rates and subject characteristics. Seventy-four men and 18 women performed up to four transfers independently from their wheelchair to a mat table while a therapist evaluated their transfer techniques using the Transfer Assessment Instrument. The highest deficit rates concerned the improper use of handgrips (63%). Other common problems included not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…in the home versus in hospital), follow-ups of more than three months, active versus standard-care control groups, evidence of a cause-and-effect relationship between training and participation outcomes and RCTs for specific populations (e.g. community-dwelling veterans with SCI, whose demographic and clinical characteristics as well as health-care experiences may be different from general populations [4042]).…”
Section: Introductionmentioning
confidence: 99%
“…in the home versus in hospital), follow-ups of more than three months, active versus standard-care control groups, evidence of a cause-and-effect relationship between training and participation outcomes and RCTs for specific populations (e.g. community-dwelling veterans with SCI, whose demographic and clinical characteristics as well as health-care experiences may be different from general populations [4042]).…”
Section: Introductionmentioning
confidence: 99%
“…5,8,9 Despite transfer training being cited as the third most used treatment during inpatient rehabilitation stays, 10 less than one quarter of individuals with thoracic-level spinal cord injuries (SCIs) report the ability to transfer independently at the time of discharge. 1,11 Even among those who can independently transfer, a 2016 study 12 found that 63% did not use a proper handgrip, 50% did not set up their wheelchair at a proper angle, and 58% transferred without removing barriers. Deficits in transfer skills have been associated with nonergonomic biomechanics and measures of pain and pathology in the upper extremities, 3,9,[13][14][15] highlighting the continued need for utilization of appropriate transfer training techniques.…”
mentioning
confidence: 99%
“…With regard to the difference in the degree of independence for transfers, one of the main reasons might be that the lateral transfer method does not require a high balancing ability or application of pedal force for interrupting the forward momentum of the body mass to prevent a fall in the forward direction during transfer. In the typical squat/stand-pivot transfer, patients must lift their buttocks to avoid hitting the armrest and wheel of the wheelchair to perform the transfer from a wheelchair to another surface [10,[20][21][22][23][24][25]. However, for LTAR, patients do not need to raise their centre of gravity and shift their centre of gravity mainly laterally along a horizontal plane [12][13][14].…”
Section: Discussionmentioning
confidence: 99%